Examining Domestic Violence Under Nigerian Law and Islamic Law - Abikan, Yahaya Ibrahim (Jurnal Syariah dan Hukum Komparatif, 2024)
The paper examined domestic violence under Nigerian law and Islamic Law. Domestic violence involves infliction of physical, sexual, or psychological harm by one spouse on the other. To achieve the aim and objectives of this research, the meaning, nature and causes of domestic violence were briefly discussed. The paper adopted a doctrinal research method by conducting an in-depth analysis of the Violence Against Persons (Prohibition) Act, 2015, some Qur’anic provisions, prophetic traditions and juristic opinions relating to the topic. The paper critically examined and analyzed Chapter 4, verse 34 of the Holy Qur’an to find out whether or not its provision permits, condones or endorses domestic violence against women. The study found that this Qur’anic verse does not encourage, condone, endorse or permit domestic violence in whatever form. It further found that the beating mentioned in the verse is a non-violent symbolic gesture. The major findings are that Islam prohibits and condemns any form of domestic violence against women, and the principles of compassion, mercy, and respect for human dignity are central to Islamic teaching. The paper recommended collaborative efforts of the government and religious leaders to campaign against and condemn domestic violence in whatever form and all ramifications.